2020
DOI: 10.3390/ma13051176
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Biogenic Passivating Layers on Corroded Iron

Abstract: This study evaluates mechanisms of biogenic mineral formation induced by bacterial iron reduction for the stabilization of corroded iron. As an example, the Desulfitobacterium hafniense strain TCE1 was employed to treat corroded coupons presenting urban natural atmospheric corrosion, and spectroscopic investigations were performed on the samples’ cross-sections to evaluate the corrosion stratigraphy. The treated samples presented a protective continuous layer of iron phosphates (vivianite Fe2+3(PO4)2·8H2O and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…To this purpose, previous studies demonstrated the efficacy and reliability of microorganisms exploited in conservation treatments (Junier and Joseph, 2017). Studies aiming to achieve stabilization of iron and copper archaeological artefacts using biomineralization revealed the additional potential of the selected microorganisms to remove undesired corrosion, achieving the so-called "bio-cleaning" of the metallic substrates (Comensoli et al, 2019). Nevertheless, the use of living organisms is tricky to be implemented in everyday CRs praxis, therefore research is also evaluating the use of metabolites that are extracted from microorganisms, such as siderophore chelators (Albelda-Berenguer et al, 2019;Cuvillier et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To this purpose, previous studies demonstrated the efficacy and reliability of microorganisms exploited in conservation treatments (Junier and Joseph, 2017). Studies aiming to achieve stabilization of iron and copper archaeological artefacts using biomineralization revealed the additional potential of the selected microorganisms to remove undesired corrosion, achieving the so-called "bio-cleaning" of the metallic substrates (Comensoli et al, 2019). Nevertheless, the use of living organisms is tricky to be implemented in everyday CRs praxis, therefore research is also evaluating the use of metabolites that are extracted from microorganisms, such as siderophore chelators (Albelda-Berenguer et al, 2019;Cuvillier et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have been conducted on the ability of bacteria to induce mineral precipitation in both natural environments and controlled laboratory conditions [10][11][12][13][14][15]. Microbial metabolism can convert Ca 2+ ions, Mg 2+ ions, and iron ions (Fe 2+ and Fe 3+ ) in the surrounding environment into carbonate, sulfate, sulfide, oxide, and other forms of minerals [16][17][18][19][20][21][22]. As for Synechocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…From the practical point of view, the corrosion test is carried out in artifi cially created conditions which imitate natural conditions. The acceleration of the corrosion processes in comparison with the operating conditions might be established by the changed conditions in the specially designed chambers or appratus 3 . The tests on the laboratory scale are realized using coupons which are placed in the liquids (the industrial liquids or the perpetrated solutions in the laboratory conditions).…”
Section: Introductionmentioning
confidence: 99%